Nitroheterocyclic drug resistance mechanisms in Trypanosoma brucei. (17th November 2015) - Wyllie, Susan; Foth, Bernardo J.; Kelner, Anna; Sokolova, Antoaneta Y.; Berriman, Matthew; Fairlamb, Alan H.
Abstract: Objectives: The objective of this study was to identify the mechanisms of resistance to nifurtimox and fexinidazole in African trypanosomes. Methods: Bloodstream-form Trypanosoma brucei were selected for resistance to nifurtimox and fexinidazole by stepwise exposure to increasing drug concentrations. Clones were subjected to WGS to identify putative resistance genes. Transgenic parasites modulating expression of genes of interest were generated and drug susceptibility phenotypes determined. Results: Nifurtimox-resistant (NfxR) and fexinidazole-resistant (FxR) parasites shared reciprocal cross-resistance suggestive of a common mechanism of action. Previously, a type I nitroreductase (NTR) has been implicated in nitro drug activation. WGS of resistant clones revealed that NfxR parasites had lost >100 kb from one copy of chromosome 7, rendering them hemizygous for NTR as well as over 30 other genes. FxR parasites retained both copies of NTR, but lost >70 kb downstream of one NTR allele, decreasing NTR transcription by half. A single knockout line of NTR displayed 1.6- and 1.9-fold resistance to nifurtimox and fexinidazole, respectively. Since NfxR and FxR parasites are ∼6- and 20-fold resistant to nifurtimox and fexinidazole, respectively, additional factors must be involved. Overexpression and knockout studies ruled out a role for a putative oxidoreductase (Tb927.7.7410) and a hypothetical gene (Tb927.1.1050), previously identified in a genome-scale RNAi screen. Conclusions: NTR was confirmed as a key resistance determinant, either by loss of one gene copy or loss of gene expression. Further work is required to identify which of the many dozens of SNPs identified in the drug-resistant cell lines contribute to the overall resistance phenotype.